Reading Strategies: The Employment in Academic Reading and The Teaching Way - Faricha Rizqi; Joko Nurkamto; Abdul Asib (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2018)
Reading is deemed to have great significance to develop other skills such as writing, speaking, and listening. It provides information and knowledge from a source in the written form. Moreover, reading and comprehension take place not only in the realm of education but in every field of life. Therefore, foreign language learners are supposed to be introduced with reading strategies in order to have successful reading comprehension as the essence of reading. This study explored the type and the frequency of the employment of reading strategies in academic reading. This was done through the instrument developed by Mokhtari and Sheorey (2002), the students’ preferred reading strategy was revealed. Additionally, the teacher’s method of teaching reading strategies was also explored.